A Vitamin Pattern Diet Is Associated with Decreased Risk of Gestational Diabetes Mellitus in Chinese Women: Results from a Case Control Study in Taiyuan, China - Qiong Chen; Yongliang Feng; Hailan Yang; Weiwei Wu; Ping Zhang; Keke Wang; Ying Wang; Jamie Ko; Jiaxin Shen; Lingling Guo; Feng Zhao; Wenqiong Du; et al. (Journal of Diabetes Research)
Identification of modifiable dietary factors, which are involved in the development of gestational diabetes mellitus (GDM), could inform strategies to prevent GDM. Therefore, we examined the dietary nutrient patterns and evaluated their relationship with GDM risk in a Chinese population using a case control study design. A total of 1,464 GDM cases and 8,092 non-GDM controls were included in the final analysis. Dietary intake was assessed using a 33-item food frequency questionnaire, and nutrients were estimated using the Chinese Standard Tables of Food Consumption. Dietary nutrient patterns were identified using factor analysis, and their associations with GDM risk were evaluated using unconditional logistic regression models adjusting for total energy intake, maternal age, high blood pressure, education, maternal body mass index (BMI), parity, and family history of diabetes. A “vitamin” nutrient pattern was characterized as the consumption of diet rich in vitamin A, carotene, vitamin B2, vitamin B6, vitamin C, dietary fiber, folate, calcium, and potassium. For every quartile increase in the vitamin factor score during one year prior to conception, the first trimester, and the second trimester of pregnancy, the GDM risk decreased by 9% (OR: 0.91, 95%CI: 0.86-0.96), 9% (OR: 0.91, 95%CI: 0.86-0.96), and 10% (OR: 0.90, 95%CI: 0.85-0.95), respectively. The significant reduced GDM risk was seen in women regardless of age and parity, and slightly stronger effect was found in women whose age≤30 and women who are nulliparous across the three time periods. The significant association was also found in women whose BMI≤24 with similar effect size across the three time periods. Our study suggests that the vitamin nutrient pattern diet is associated with decreased GDM risk. Additional studies are necessary to explore the underlying mechanism of this relationship.